Naloxone-precipitated mitragynine withdrawal did not associate with increased anxiety-like behaviour in rats - Harun, Norsyifa; Johari, Illa Syafiqah; Japarin, Rima Atria; Syuhadaa Bakar, Siti Najmi; Mat, Noorul Hamizah; Hassan, Zurina; Hassan, Haniza (Malaysian Society for Biochemistry & Molecular Biology, 2021)
Kratom (Mitragyna speciosa Korth) is a plant species currently used as an alternative self-treatment for pain and management of opioid dependence and withdrawal. However, information on the effect of its negative emotional state of withdrawal, particularly of the main psychoactive constituent, mitragynine (MG) is still lacking. The present study was designed to determine whether naloxone-precipitated MG withdrawal is associated with increased anxiety-like behaviour in both open-field test (OFT) and elevated-plus maze (EPM) test. Male Sprague Dawley rats were administered with MG and morphine twice daily for 14 consecutive days to develop substance dependence. The withdrawal was precipitated on day fifteen using naloxone (2 mg/kg, i.p.). This study has exhibited that challenge with opioid antagonist naloxone did not result in reliable expression of anxiety behaviour following chronic MG exposure in OFT and EPM tests. However, several somatic signs of withdrawal were observed in naloxone-precipitated MG withdrawn rats. The findings of this study suggest that rat behaviours during OFT and EPM tests might not be driven solely by anxiety levels following naloxone-precipitated withdrawal but rather by other withdrawal-induced behaviours. The presence of somatic signs in naloxoneprecipitated MG withdrawn rats was the piece of evidence to prove that that discontinuation of MG or kratom is associated with physical symptoms of withdrawal. However, further studies are prompted to evaluate MG or kratom withdrawal severity to justify its use as opioid replacement therapy.